Socrates, Vlastos, Scanlon and the Principle of the Sovereignty of Virtue - Nascimento, Daniel Simão (Revista Archai, 2020)
This article offers a new formulation of the Socratic principle known as the Principle of the Sovereignty of Virtue (PSV). It is divided in three sections. In the first section I criticize Vlastos’ formulation of the PSV. In the second section I present the weighing model of practical deliberation, introduce the concepts of reason for action, simple reason, sufficient reason and conclusive reason that were offered by Thomas Scanlon in Being realistic about reasons (2014), and then I adapt these concepts so as to render them apt to be used in the formulation I intend to offer. In the third section I present my formulation of the PSV using the concepts introduced in the second section and explain why I believe this formulation is better than the one offered by Vlastos.